Clarification of the systematic position of Patula spatiosa Lindholm, 1922 from eastern Turkey (Mollusca: Gastropoda) - Walther, Frank; Neiber, Marco T. (Zootaxa, 2018)
One of the most mysterious taxa of the terrestrial snail fauna of Turkey is Patula spatiosa Lindholm, 1922. This large species has been described from a single specimen collected in 1914 allegedly in the Kars region (nowadays easternmost Turkey). Up to date, no further specimens have been reported. Its taxonomical position is unclear, even on the family level.